Нові види Leccinum Gray (Boletaceae) в Україні - Гелюта, В.П.; Висоцька, О.П.; Бесєдіна, І.С. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Приводится информация о распространении новых для Украины видов Leccinum quercinum (Pilбt) E.E. Green et Watling и L. vulpinum Watling (Boletales). Дается их краткая характеристика. Brief descriptions and information about distribution of Leccinum quercinum (Pildt) E.E. Green et Watling and L. vulpinum Watling (Boletales), new species for Ukraine, are given.